Integrating future land use uncertainty and spatial scales into ecosystem service degradation risk assessment for urban ecological management - Li, Yan; Wu, Hao; Blaschke, Thomas; Pradhan, Biswajeet; Mohamed Shariff, Abdul Rashid Bin; Avtar, Ram; Lin, Anqi; Shao, Wenting (Elsevier, 2026)
Rapid land-use change has imposed substantial pressures on urban ecosystems, underscoring the need to assess ecosystem service degradation risks (ESDR) to promote urban ecological sustainability. However, existing studies have largely focused on comparing ESDR under multiple land-use scenarios or integrating multi-scenario ESDR based on economic theory, often overlooking the constraints introduced by land-use planning policies and the influence of spatial scale on assessment accuracy. To address these challenges, this study proposed a novel ESDR assessment framework that integrates ecosystem service value losses from multiple land-use scenarios with an optimal spatial scale, particularly aligning with future territorial spatial planning. Using Wuhan as a case, this study optimized land-use quantity and spatial pattern across future scenarios, calibrated the optimal assessment scale, and identified ESDR areas following the city's main functional zones. The results indicated notable ecological degradation in Wuhan from 2000 to 2020, while ecological degradation is expected to reverse under all three optimized land-use scenarios for 2035. At the optimal scale of 400 m, key ESDR prevention areas accounted for 10.71 % of the city, predominantly located in the peripheral regions of the central urban area and along the Sheshui River in the north, notably in the Hongshan, Caidian, Huangpi, and Jiangxia districts. Differentiated ecological management strategies should be formulated according to ESDR zones. This study effectively bridges planning policies with ESDR assessment and enables precise spatial targeting for ecological risk prevention, thereby supporting fine-grained urban ecological governance.